Is the rate of re-operation after primary lumbar microdiscectomy affected by surgeon grade or intra-operative lavage of the disc space?. (April 2014) - Ellenbogen, Jonathan R.; Marlow, William; Fischer, Benjamin E.; Tsegaye, Magnum; Wilby, Martin J.
Abstract Study design. Retrospective audit of consecutive patients. Objective. To investigate the re-operation rate following elective primary lumbar microdiscectomy and to determine whether principal surgeon grade and/or disc space lavage is a factor in recurrence. Summary of background data. Recurrent herniation of disc material following lumbar microdiscecomy surgery is one of the commonest complications of the procedure. Any reduction in the number of revision microdiscectomies performed per year would have a significant impact on patients' lives and on the health service economy. We undertook this study to ascertain whether principal surgeon grade and/or disc space lavage has an impact in reducing the re-operation rate. Methods. We undertook a retrospective audit of patients who underwent elective primary lumbar microdiscectomy, over a 3-year period (n = 971). Results. The overall re-operation rate for primary elective microdiscectomy was 3.8%, consistent with the published literature. The relative risk of re-operation in patients primarily operated by registrar surgeons was 1.2 fold the risk in patients operated by consultants (95% CI: 0.62, 2.35) although not statistically significant (p = 0.568). The risk of re-operation in the 'non lavage' group was 2.15 times the risk in the 'lavage' group (95% CI: 0.63, 7.34), but it did not reach significance (p = 0.222). Conclusions. Principal surgeon grade and intervertebral disc lavage have not been found conclusively to be factors in the rate of recurrence. This information is useful to reassure patients that their outcome from such surgery is not dependent on the grade of surgeon performing the operation. There is a possible trend towards intervertebral disc lavage reducing the rate of recurrence.